Bacteriocin-Like Inhibitory Substances in Staphylococci of Different Origins and Species With Activity Against Relevant Pathogens - Fernández-Fernández, Rosa; Lozano, Carmen; Eguizábal, Paula; Ruiz-Ripa, Laura; Martínez-Álvarez, Sandra; Abdullahi, Idris Nasir; Zarazaga, Myriam; Torres, Carmen (Frontiers in Microbiology, 2022)
Bacteriocins are antimicrobial peptides with relevance in the modulation of human and animal microbiota that have gain interest in biomedical and biotechnological applications. In this study, the production of bacteriocin-like inhibitory substances (BLIS) was tested among a collection of 890 staphylococci of different origins (humans, animals, food and the environment) and species, both coagulase-positive- (CoPS, 238 isolates of 3 species) and coagulase-negative-staphylococci (CoNS, 652 isolates of 26 species). Sixty of the 890 staphylococci (6.7%) showed antimicrobial activity by the spot-on-lawn method against at least one of the 25 indicator bacteria tested. BLIS producer (BLIS+) isolates were detected in 8.8% of CoPS and in 6.0% of CoNS. The species with the highest percentages of BLIS+ isolates were: S. chromogenes (38.5%), S. pseudintermedius (26.7%) and S. warneri (23.1%). The production of BLIS was more frequently detected among isolates of pets, wild animals and food. Moreover, 13 BLIS+ isolates showed high or medium antimicrobial activity and 7 of these isolates (of species S. aureus, S. pseudintermedius, S. sciuri, and S hominis) demonstrated antimicrobial activity against more than 70% of the indicator bacteria tested. The genetic characterization (by PCR and sequencing) of the 60 BLIS+ isolates revealed the detection of: a) 11 CoNS and CoPS isolates carrying putative lantibiotic-like genes; b) 2 S. pseudintermedius isolates harbouring the genes of BacSp222-bacteriocin; and c) 2 S. chromogenes isolates which presented the gene of a putative cyclic bacteriocin (uberolysin-like), being the first report in this CoNS species. Antimicrobial susceptibility testing was performed in BLIS+ isolates and one-third of the CoNS isolates showed susceptibility to all antibiotics tested, that also lacked the virulence genes studied. These BLIS+ CoNS could be considered as good candidates for further characterization studies.